Care-educational technologies: an emerging concept of the praxis of nurses in a hospital context - Cléton Salbego; Elisabeta Albertina Nietsche; Elizabeth Teixeira; Nara Marilene Oliveira Girardon-Perlini; Camila Fernandes Wild; Silomar Ilha
ABSTRACT Objective: to know the praxis of nurses in the hospital context and, from this, to define a concept about Care-Educational Technologies. Method: qualitative, exploratory-descriptive research, developed in a university hospital in Rio Grande do Sul State, Brazil, with 21 nurses (non-probabilistic sampling), through non-participant observation and semi-structured interview, conducted from March to December 2015. Records were analyzed through content analysis. Results: the results showed that in the context of nurses' work, it is possible to deduce care-educational possibilities, based on the person-person, person-tool and/or person-universe relationship. The concept was defined based on the intertwining of caring-training and training-caring for oneself and other people. Final considerations: the reflections point to the need to develop or strengthen the autonomy of those involved in the health-disease process. This is based on the empowerment of people under their lives' conditions, in their multidimensionality, within human praxis.